Does the use of conventional complete dentures influence taste perception? A systematic review - Avelino, Maria Eduarda Lemos; Vila-Nova, Taciana Emília Leite; Costa, Rayanna Thayse Florêncio; Pellizzer, Eduardo Piza [UNESP]; Vasconcelos, Belmiro Cavalcanti do Egito; Moraes, Sandra Lúcia Dantas (Elsevier, 2023)
Statement of problem: Although conventional complete dentures are widely used, a systematic review of their influence on wearers' taste perception is lacking. Purpose: The purpose of this systematic review was to determine whether conventional complete dentures influence the taste perception of edentulous patients. Material and methods: This systematic review was registered in the International Prospective Register of Systematic Reviews (PROSPERO) (CRD42022341567), and the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) were followed. The guiding question was: “Does the use of complete dentures influence the taste perception of edentulous patients?” Two reviewers searched articles in the PubMed/MEDLINE, Scopus, Cochrane Library, and https://clinicaltrials.gov databases up to June 2022. The risk of bias in each study was assessed using the risk of bias in nonrandomized studies of interventions and the risk of bias based on the Cochrane risk of bias tool for randomized trials. The certainty of evidence was assessed using grading of recommendations, assessment, development, and evaluation (GRADE). Results: A total of 883 articles were found with the search, and 7 were included in this review. Various changes in taste perception were identified in some of these studies. Conclusions: The use of conventional complete dentures can influence the perception of the 4 primary tastes (sweet, salty, sour, and bitter) of edentulous patients, which may negatively interfere with the perception of flavor.